Gender equality needs critical consideration in conflict-affected settings - Richards, Esther; Percival, Valerie; Ssali, Sarah; Theobald, Sally (Development in Practice, 2015)
The World Bank’s 2012 World Development Report calls for gender equality on a global level but falls short on its analysis of conflict-affected contexts. It is critical that we understand the needs of vulnerable populations in these settings. This viewpoint draws on findings from research in health reform in conflict-affected contexts to highlight some opportunities and challenges for addressing gender equality in these settings, using the policy priorities outlined in the World Bank report. Drawing on this analysis we argue that more attention and action should be focused on addressing gender inequalities and inequities in neglected conflict-affected states.
Keywords: Conflict and reconstruction; Gender and diversity; Social sector – Health; Governance and public policy